2020
DOI: 10.3390/polym12102350
|View full text |Cite
|
Sign up to set email alerts
|

Three-Step Synthesis of a Redox-Responsive Blend of PEG–block–PLA and PLA and Application to the Nanoencapsulation of Retinol

Abstract: Smart polymeric nanocarriers have been developed to deliver therapeutic agents directly to the intended site of action, with superior efficacy. Herein, a mixture of poly(lactide) (PLA) and redox-responsive poly(ethylene glycol)–block–poly(lactide) (PEG–block–PLA) containing a disulfide bond was synthesized in three steps. The nanoprecipitation method was used to prepare an aqueous suspension of polymeric nanocarriers with a hydrodynamic diameter close to 100 nm. Retinol, an anti-aging agent very common in cosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…This is not discussed in the literature yet but has an important impact on the industrial feasibility of the systems. Our recent results indicated that the SDDS made of only 33% of the redox responsive mPEG-SS-PLA polymers were active in vitro [ 124 ]. Thus, the use of a mixture of stimuli-responsive and neutral polymers could be a way to control the SDDS cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not discussed in the literature yet but has an important impact on the industrial feasibility of the systems. Our recent results indicated that the SDDS made of only 33% of the redox responsive mPEG-SS-PLA polymers were active in vitro [ 124 ]. Thus, the use of a mixture of stimuli-responsive and neutral polymers could be a way to control the SDDS cost.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of disulfide bonds incorporation was used by our group [ 124 ] in order to develop redox-responsive nanoparticles for topical applications. Briefly, a mixture of poly(lactide) (PLA) and redox-responsive poly(ethylene glycol)-block-poly(lactide) (PEG-block-PLA) containing a disulfide bond was synthesized in three steps.…”
Section: Polymer-based Smart Drug Delivery Systems For Topical Applicationsmentioning
confidence: 99%
“…Lately, a method to synthesize a redox-responsive blend of mPEG-b-PLA/PLA polymers was developed in our laboratory [ 19 ]. Briefly, a blend of redox-responsive mPEG-SS-PLA copolymer and a non-responsive PLA polymer (ratio 1:2) was synthesized in three steps and used for retinol encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is prominent in the emerging bio-plastics market [3,4]. However, PLA is insufficient for most commercial applications, especially in engineering fields such as the automotive industry, because of its innate shortcomings (such as brittleness, slow rate of crystallization, and hydrolysis [5,6]). The mechanical performance of polymers depends on several parameters such as the enhance phase, interface compatibility and the preparation technology [7][8][9].…”
Section: Introductionmentioning
confidence: 99%